Risk of malignancies using anti-TNF agents in rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis: a systematic review and meta-analysis. Issue 1 (5th December 2016) - Bonovas, Stefanos; Minozzi, Silvia; Lytras, Theodore; González-Lorenzo, Marien; Pecoraro, Valentina; Colombo, Silvia; Polloni, Ilaria; Moja, Lorenzo; Cinquini, Michela; Marino, Valentina; Goletti, Delia; Matucci, Andrea; et al.
ABSTRACT: Introduction: Malignancies have been reported in patients with rheumatoid arthritis, psoriatic arthritis and ankylosing spondylitis, treated with anti-tumour necrosis factor (anti-TNF) agents. Areas covered: We conducted a systematic review of randomized controlled trials (RCTs) to determine the effect of anti-TNF agents on the occurrence of cancer (any type). Literature databases were searched up to May 2014 to identify relevant studies that evaluated adalimumab, certolizumab, etanercept, golimumab, or infliximab, compared with placebo or no treatment. Data on cancer occurrence were extracted at the maximum follow-up time reported. Expert opinion: Fifty-five RCTs with 20, 631 patients met the eligibility criteria. Of these, 32 trials with 15, 539 patients reported at least one case of cancer, for a total of 112 malignancies. The degree of variability between studies was consistent with what would be expected to occur by chance alone. There was no evidence of an association between anti-TNF agents and cancer risk (fixed-effects model (OR: 1.31, 95% CI: 0.89, 1.95); a random-effects model (OR: 1.16, 95% CI: 0.75, 1.81)). We found evidence of selective outcome reporting or publication bias suggesting that the pooled effect estimate for cancer may have been overestimated. The evidence is imprecise, and the risk of bias was high or unclear across primary studies.